2017
DOI: 10.3389/fped.2017.00002
|View full text |Cite
|
Sign up to set email alerts
|

Airway-Clearance Techniques in Children and Adolescents with Chronic Suppurative Lung Disease and Bronchiectasis

Abstract: Common symptoms of chronic suppurative lung disease or bronchiectasis in children and adolescents are chronic cough with sputum production, retention of excess secretions in dilated airways, and a history of recurrent infections. Clinical management includes the prescription of airway-clearance techniques (ACTs) to facilitate mucociliary clearance, optimize sputum expectoration, relieve symptoms, and improve well-being. A wide range of ACTs are available for selection, and these strategies may be applied in is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 52 publications
2
36
0
1
Order By: Relevance
“…All of these programmes included lower and upper limb exercises and strengthening exercises and were tailored to the individual patient's capabilities. In children, exercise (especially endurance exercise) is helpful and some experts have also suggested that singing may have a salutatory effect in children …”
Section: Pr In Bronchiectasismentioning
confidence: 99%
See 3 more Smart Citations
“…All of these programmes included lower and upper limb exercises and strengthening exercises and were tailored to the individual patient's capabilities. In children, exercise (especially endurance exercise) is helpful and some experts have also suggested that singing may have a salutatory effect in children …”
Section: Pr In Bronchiectasismentioning
confidence: 99%
“…For children with bronchiectasis, the principles of ACT in current practice follow what has been described in adults, given the paucity of research which exists. 36 Questions remain around how airway clearance relates to key clinical outcomes in bronchiectasis in both adults and children. 6,36 Crucially, there is no strong evidence to inform choice, frequency or duration of ACT in bronchiectasis.…”
Section: Airway Clearance In Bronchiectasismentioning
confidence: 99%
See 2 more Smart Citations
“…There is limited evidence that the active breathing cycles and flutter are superior in the gravity-assisted position compared with the sitting position. [ 206 207 208 ]…”
Section: Airway Clearance Techniquementioning
confidence: 99%